AN INVESTIGATION INTO SYNTACTIC AND PRAGMATIC FEATURES OF CRITICISMS USED IN ENTERTAINMENT PROGRAMS ON TV IN ENGLISH AND VIETNAMESE - Bùi Thị Thanh Minh (2025)
This thesis deals with criticisms used in TV Entertainment Programs in English and Vietnamese in terms of the syntactic and pragmatic features in the two languages. The data of the study was collected from many different websites in English and Vietnamese languages such as www.addic7ed.com; www.youtube.com; www.americanidol.com; www.vietnamgottalent.com; www.vietnamidol.com, etc. with 200 criticisms samples in English and 200 ones in Vietnamese. The data was then described on the syntactic and pragmatic domains and contrastively analysed under qualitative and quantitative approaches, descriptive method, analytic method, constrative method. The samples collected by reading transcripts of prestigious American and Vietnamese entertainment programs as well as watching video clips on youtube or on TV. The findings of the study show that there are similarities and differences in both syntactic and pragmatic features of criticisms in the two languages. These similarities and differences will be the background for the consideration of English teaching application in actual communication. Teaching the functions of criticisms should include the exploitation of its syntactic and pragmatic aspects. This will help learners deeply and fully understand the superficial as well as the implied meanings of criticisms.